IMPLEMENTASI KEBIJAKAN PENGELOLAAN KEAMANAN DI WILAYAH PERBATASAN OLEH TNI UNTUK MENCEGAH KEJAHATAN LINTAS BATAS DI PULAU SEBATIK - Muammar Irfan Aulia (HI 16 UMY 194, 2016)
*194 Transnational crime in the border area of Sebatik Island potentially disrupt security and the territorial integrity of Indonesia. Mandate of Constitution 1945, Indonesian national goal is to protect the entire Indonesian nation and the entire country of Indonesia. To realize the national objectives will be established TNI as an instrument of national defense. Management of security in the border area is set within the Border Management Plan prepared by the National Agency for Border Management (BNPP). This study aims to explain how the implementation of border management policy by the Army to prevent transnational crime in Sebatik Island, Nunukan, Kalimantan Utara. Research methodology through the library (Library Research) and field (Field Work Research), which consists of surveys and interviews, which were described. The conclusion of this study is the Army implements a security management plan in the border regions which have been prepared by BNPP in the form of activities that are tailored to the duties and functions of the military in the Constitution of the Republic of Indonesia Number 34 Year 2004 on the Indonesian National Army.